Guest Editors’ Introduction: Ethical Management of Intangible Assets in Contemporary Organizations - Gambetti, Rossella C. (Business ethics quarterly, 2017)
This essay explains how intangible asset management oriented toward enhancing corporate performance increasingly embeds ethical concerns, primarily to address stakeholder expectations. We discuss how ethical dimensions in intangible asset management may be co-constructed and intertwined in organization-stakeholder interactions to generate collaborative meaning making according to a stakeholder-centric view of the firm. In so doing, we adopt an ethical view that acknowledges that stakeholders beyond the firm have equal status and agency to engage in a social construction process of intangible assets nurtured by ongoing dialogue and reciprocal understanding between organization and stakeholders. The essay concludes by envisioning how the dialogic process of social construction of intangible assets involving both organization and stakeholders is best conceived as a social contract between the two that enacts a cultural bond between intangible assets together with ethical and societal resources that are collectively generated, owned, and maintained.